Epidemiology and predictive factors for early and late mortality in Candida bloodstream infections: a population‐based surveillance in Spain. (11th October 2013) - Puig‐Asensio, M.; Padilla, B.; Garnacho‐Montero, J.; Zaragoza, O.; Aguado, J. M.; Zaragoza, R.; Montejo, M.; Muñoz, P.; Ruiz‐Camps, I.; Cuenca‐Estrella, M.; Almirante, B.; ,; et al.
Abstract A prospective, multicentre, population‐based surveillance programme for Candida bloodstream infections was implemented in five metropolitan areas of Spain to determine its incidence and the prevalence of antifungal resistance, and to identify predictors of death. Between May 2010 and April 2011, Candida isolates were centralized to a reference laboratory for species identification by DNA sequencing and for susceptibility testing by EUCAST reference procedure. Prognostic factors associated with early (0–7 days) and late (8–30 days) death were analysed using logistic regression modelling. We detected 773 episodes: annual incidence of 8.1 cases/100 000 inhabitants, 0.89/1000 admissions and 1.36/10 000 patient‐days. Highest incidence was found in infants younger than 1 year (96.4/100 000 inhabitants). Candida albicans was the predominant species (45.4%), followed by Candida parapsilosis (24.9%), Candida glabrata (13.4%) and Candida tropicalis (7.7%). Overall, 79% of Candida isolates were susceptible to fluconazole. Cumulative mortality at 7 and 30 days after the first episode of candidaemia was 12.8% and 30.6%, respectively. Multivariate analysis showed that therapeutic measures within the first 48 h may improve early mortality: antifungal treatment (OR 0.51, 95% CI 0.27–0.95) and central venous catheter removal (OR 0.43, 95% CI 0.21–0.87). Predictors of late death included host factors (e.g. patients' comorbid status and signs of organ dysfunction), primary source (OR 1.63, 95% CI 1.03–2.61), and severe sepsis or septic shock (OR 1.77, 95% CI 1.05–3.00). In Spain, the proportion of Candida isolates non‐susceptible to fluconazole is higher than in previous reports. Early mortality may be improved with strict adherence to guidelines.